Teachers’ Behaviour and Student Academic Performance in Commerce in Public Secondary Schools in Ibadan North Local Government Area of Oyo State, Nigeria - Arinola O. Olaleye (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study examined teachers’ behaviour and student academic performance in commerce in public secondary schools in Ibadan North Local Government Area of Oyo State. Two research questions were raised and two hypotheses were formulated. Descriptive survey research design was employed. Population comprised 730 senior secondary school commerce students in 7 selected public schools in the LGA. 258 students were sampled using Yamane sample size formula. Primary data were collected using a self-developed questionnaire titled: “Teachers’ Behaviour and Academic Performance Questionnaire” (TBAPQ, r = .813)”. Data were analysed using descriptive and inferential statistics. Results showed there is a moderate level of teachers’ classroom discipline (x̅= 2.858) and teachers’ instructional methods (x̅= 2.512) on students’ academic performance. Test of hypotheses showed a positive significant relationship between teachers’ classroom discipline and students’ academic performance (r = .334, P< 0.05) and between teachers’ instructional methods and students’ academic performance (r = .297, P< 0.05). In conclusion, teachers’ behaviour in areas of classroom discipline and instructional methods have a significant relationship on students’ academic performance in Commerce. It was recommended among others that teachers should be equipped through supervision and training to enhance their classroom discipline and instructional methods for better academic performance of the students in commerce.